Isogeometric Methods for Numerical Simulation - Beer, Gernot (Springer, 2015)
The book presents the state of the art in isogeometric modeling and shows how the method has advantaged. First an introduction to geometric modeling with NURBS and T-splines is given followed by the implementation into computer software. The implementation in both the FEM and BEM is discussed.